PENGARUH PENERAPAN LATTICE MULTIPLICATION METHOD UNTUK MENGATASI KESULITAN MENYELESAIKAN OPERASI PERKALIAN - Fatmala, Farlina Wardiyana; Muzaki, Ahmad; Pujilestari, Pujilestari (Media Pendidikan Matematika, 2018)
The purpose of this study was determine the effect of application of lattice multiplication method to overcome the difficulties of completing mathematical multiplication and anxiety operations in grade VIII of SMPN 7 Pujut. The method used in this study wasÂ  pre-experimental research method with one group pre and posttest design research design. The sample of this study was representative of students from each class in grade VIII of SMPN 7 Pujut, it was recommended by mathematics teachers because they had difficulty completing multiplication operations, about 20 students. Based on the results of the study, the mean difference in the percentage of the initial results mathematical anxiety questionnaire with the final result was from 56.37% decreased to 42.65%, which were both still in the sufficient category. Furthermore, by testing the hypothesis using the t test (paired sample t test) assisted by SPSS 16.0 obtained data tcount = 0,000 and with a = 5% = 0.05 obtained ttable = 1.729 which means tcount Â ttable. These results indicate that there were significant differences between the results of the test before applying the lattice multiplication method (pretest) with the results after the application of the lattice multiplication method (posttest) obtained by students. Thus it can be concluded that there was a rejection of H0 so that Ha is accepted, where Ha reads: there was an effect of the application of lattice multiplication method to overcome the difficulties of completing mathematical multiplication and anxiety operations in grade VIII of SMPN 7 Pujut.